Analisis Faktor Kepuasan Pengguna Layanan Website SKCK Online Menggunakan Metode End User Computing Satisfaction (EUCS) - Yanuar Nurdiansyah; Eka Putri Agustini Wulandari; Diah Ayu Retnani Wulandari (Faculty of Computer Science, University of Jember, 2020)
One of the main duties of the police is to provide services to the community, namely the preparation of Police Record Certificate (SKCK). Making SKCK based online to facilitate the community in making SKCK. But there are some online SKCK users, there are still many problems that arise and criticism of online SKCK. Therefore it is necessary to measure the level of satisfaction and analyze the factors that affect user satisfaction with online SKCK. This study uses the End User Computing Satisfaction (EUCS) method. This type of research is quantitative by distributing questionnaires to SKCK registrants in the Banyuwangi area. Data analysis was carried out by using valid test, reliable test, descriptive statistical test, F test and T test using SPSS 22. The results of the descriptive test with the Likert scale in order of the largest, namely the content variable with a percentage of 85.4%, are included in the Very Satisfied category, the 80.4% timeliness variable is included in the Very Satisfied category, the 75.8% ease of use variable is included in the Satisfied category, the 73.2% format variable is included in the Satisfied category and 67.5% accuracy variable is included in the Satisfied category.